Young-Onset Carcinogenesis – The Potential Impact of Perinatal and Early Life Metabolic Influences on the Epigenome - Barreto, Savio George; Pandol, Stephen J. (Frontiers in Oncology, 2021)
The last decade has witnessed a significant rise in cancers in young adults. This spectrum of solid organ cancers occurring in individuals under the age of 40 years (some reports extending the age-group to <50 years) in whom aetiology of cancer cannot be traced back to pre-existing familial cancer syndromes, is referred to as termed young-, or early- onset cancers. The underlying causes for young-onset carcinogenesis have remained speculative. We recently proposed a hypothesis to explain the causation of this entity. We propose that the risk for young-onset cancer begins in the perinatal period as a result of the exposure of the foetus to stressors, including maternal malnutrition, smoking or alcohol, with the consequent epigenomic events triggered to help the foetus cope / adapt. Exposure to the same stressors, early in the life of that individual, facilitates a re-activation of these ‘responses designed to be protective’ but ultimately resulting in a loss of regulation at a metabolic and / or genetic level culminating in the evolution of the neoplastic process. In this manuscript, we will provide a rationale for this hypothesis and present evidence to further support it by clarifying the pathways involved, including elucidating a role for Acetyl-CoA and its effect on the epigenome. We present strategies and experimental models that can be used to test the hypothesis. We believe that a concerted effort by experts in different, but complementary fields, such as epidemiology, genetics, and epigenetics united towards the common goal of deciphering the underlying cause for young-onset cancers is the urgent need. Such efforts might serve to prove, or disprove, the presented hypothesis. However, the more important aim is to develop strategies to reverse the disturbing trend of the rise in young-onset cancers.